Fully Automated One-Step Production of Functional 3D Tumor Spheroids for High-Content Screening. (April 2016) - Monjaret, François; Fernandes, Mathieu; Duchemin-Pelletier, Eve; Argento, Amelie; Degot, Sébastien; Young, Joanne
Adoption of spheroids within high-content screening (HCS) has lagged behind high-throughput screening (HTS) due to issues with running complex assays on large three-dimensional (3D) structures. To enable multiplexed imaging and analysis of spheroids, different cancer cell lines were grown in 3D on micropatterned 96-well plates with automated production of nine uniform spheroids per well. Spheroids achieve diameters of up to 600 µm, and reproducibility was experimentally validated (interwell and interplate CVdiameter <5%). Biphoton imaging confirmed that micropatterned spheroids exhibit characteristic cell heterogeneity with distinct microregions. Furthermore, central necrosis appears at a consistent spheroid size, suggesting standardized growth. Using three reference compounds (fluorouracil, irinotecan, and staurosporine), we validated HT-29 micropatterned spheroids on an HCS platform, benchmarking against hanging-drop spheroids. Spheroid formation and imaging in a single plate accelerate assay workflow, and fixed positioning prevents structures from overlapping or sticking to the well wall, augmenting image processing reliability. Furthermore, multiple spheroids per well increase the statistical confidence sufficiently to discriminate compound mechanisms of action and generate EC50 values for endpoints of cell death, architectural change, and size within a single-pass read. Higher quality data and a more efficient HCS work chain should encourage integration of micropatterned spheroid models within fundamental research and drug discovery applications.